A survey of post-operative management for patients following first time lumbar discectomy - Williamson, Esther (Springer-Verlag, 2006)
This study aimed to identify current NHS physiotherapy practice following first time lumbar discectomy in the United Kingdom (UK) in order to inform future research priorities and design. Descriptive survey methodology was utilised employing a postal questionnaire. A total population sample was identified and questionnaires were posted to 87 NHS physiotherapy departments throughout the UK. Participants were senior physiotherapists working with spinal surgery patients. In the inpatient phase, the majority of patients receive physiotherapy. Management focused on mobility and education to facilitate early discharge with most patients being given exercises. However, there was a wide variation in the actual exercises prescribed. There was more variation in the provision of outpatient physiotherapy treatment. Not all patients have access to physiotherapy treatment post discharge in the UK and when treatment was available the content and amount was variable. There is evidence to support rehabilitation classes to assist early improvements in function and return to work but such classes are only available in around half of the centres involved in this study. Regarding the content of exercise classes and individual treatment sessions, a wide range of clinical practice was evident. This study raises many research questions and highlights the need for future research to optimise patient rehabilitation following first time lumbar discectomy.